THE CONCEPTS OF MANIS AND PAHIT IN INDONESIAN EXPRESSIONS (COGNITIVE LINGUISTIC APPROACH) - Nurul Adhalina (Universitas Aki, 2020)
Manis and pahit that are well known as the kinds of flavour are used by Indonesian to express experiences, thoughts, feelings, or anything in daily activities. It happens since special characters of these flavours have been structured in people thoughts. By means of this this study, the writer attempts to describe kinds of meaning represented by Indonesian manis and pahit expressions and also describe things of life associated with manis and pahit in Indonesian expressions. The data are manis and pahit expressions found and selected randomly from several sources. The writer uses non participants’ observation, and note taking techniques to present the data. Referential identity, distributional, reflective introspective and abductive inferential methods are also used to analyze the data. The result shows that manis and pahit in Indonesian expressions represent three kinds of meaning; connotative, metaphoric, and ironic. Manis and pahit in Indonesian expressions also associate with eleven things in life; condition, feeling, attitude, action, physical appearance, result, relationship, process, event, statement, and life.